Implementasi Kurikulum MBKM (Merdeka Belajar Kampus Merdeka) Dalam Meningkatkan Kualitas Pendidikan di Indonesia - Nizar Nizar; Reo Tomi Pratama; Mustafiyanti Mustafiyanti (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The independent curriculum is a new curriculum implemented by the ministry of education and culture as an effort to improve educational conditions after Covid-19. Curriculum change is a natural and natural process should happen as stated by Oliva (2004) "Curriculum change is inevitable and desirable.” Development of science and technology, community needs, progress times, and new government policies cause the climate to change. Life in the 21st century demands changes to the higher education system basic. The message is changes in information and communication technology, emergence the era of disruption, also causes changes to occur at a high rate in economic, social and cultural fields. In these very dynamic times, it is necessary transformation of learning to be able to equip and prepare educational graduates high in order to become a superior generation. The demands of 21st century competence place creativity and innovation as words an important key to equipping higher education graduates to be able to contribute best contribution to Indonesia's development The government, through the Minister of Education and Culture, places emphasis on universities to prepare graduates who are strong, relevant to current developments and have a high national spirit to achieve the goal of improving the quality of education in Indonesia.